A QUALITATIVE RESEARCH ON OUTPLACEMENT SERVICES - Ertemsir, Esin; celik, Derya; Kobak, Ozge; Nalbantoglu, Zeynep Sinem (Kafkas University IIBF, 2022)
Businesses that dismiss employees for corporate reasons such as downsizing, merger, restructuring, or individual reasons such as poor performance use the Outplacement Services to minimise the negative effects of this difficult process. In this setting, career counseling, job placement assistance, interview coaching etc. may be provided. In this study, interviews were performed with senior HR managers from six organizations in Turkey that provide outplacement either in-house or through consultancy firms. Business-level data were analyzed using theme analysis and qualitative descriptive analysis based on the literature. The results show that this practice turned into a routine HR process by half of the participants, and the other half utilized it systematically after mass layoffs during economic downturns. Outplacement is thought to improve the business image for both internal and external stakeholders. The duration of the service is kept more limited due to the high cost when taken from consultancy firms.
Keywords: Outplacement; offboarding; qualitative research; Business & Economics